A Comparative Study of Honda and Toyota Brands in Hybrid Vehicle Sustainability Using the Competitive Profile Matrix (CPM) Framework - Putri Karina Aginta; Nasukha Kartika Syukla; Febriyanti Maria Yosefa; Rasyid Sofiani (EPJ Web of Conferences)
Global climate change and pollution have become critical global issues, necessitating the search for sustainable solutions in various sectors, especially transportation. Sustainable transportation is smart and environmentally friendly vehicles. One example is the HEV or Hybrid Electric Vehicle, a vehicle that uses two types of power sources. This research aims to see and understand the main factors that influence consumers in making decisions to buy HEV cars, especially in the Toyota and Honda brands. This study employs a quantitative approach using surveys as the primary data collection method with targeted number of respondents is 30 per brand (total 60) to ensure data represents the target population and allows relevant statistical analysis. The findings reveal that Toyota holds a slight competitive advantage, particularly in safety perception, internal capabilities related to technology, and responsiveness to government policy and innovation. Meanwhile, Honda competes closely, excelling in cost efficiency, particularly in maintenance and affordability. The use of empirically derived weights highlights a shift in consumer priorities, with operational and maintenance costs outweighing resale value in vehicle choice decisions. While Toyota maintains a slight edge, both brands’ future differentiation will increasingly depend on their ability to respond to cost concerns, regulatory developments, and innovation cycles.